Influência da pressão nominal de contato no coeficiente de atrito estático em plano inclinado automatizado - Amaral, Pedro Luiz Fiad do (2013)
The relative movement among flat surfaces in contact is common for many engineering projects. During the operation of many mechanisms, friction problems are identified as a main obstacle to the successful performance of them. In this study the influence of nominal pressure contact on static friction between steel surfaces (ABNT 1020 and 1045) and glass plate is evaluated. The specimens‘ surfaces were obtained by means of a manufacturing process classified as machining with undefined tool – tangential plane grinding. The specimens were constituted by two groups: the group A (type cup – ABNT1010) and the group B (type compact – ABNT1045). All specimens were characterized with respect to surface roughness, using a 3-D optical non-contact profilometer. For static friction measurements, an inclined plan system was used, with an automated detection of movements of specimens along time. The nominal contact pressure not has any effect on the values of static friction coefficient. Since then, a possible effect of surface roughness on friction was investigated. The spectral moments m0, m2 and m4, and the bandwidth parameter, Alpha (α), were calculated from the 3-D roughness parameters, and this latter was correlated with static friction coefficient. Within the analyzed parameters: Sq, Sdq and Sds, the Sq parameter presented the largest discrepancy within the sampling data. Based on the statistical analysis of variance, with a confidence level of 5%, of Sq parameter, the specimens were relocated into 4 groups, for which we calculated alpha parameter. Considering these groups, we demonstrated that the alpha parameter affected the static friction coefficient, that is, the higher this parameter, the greater the static friction coefficient.